Heterochromatin protein 1 interacts with 5'UTR of transposable element ZAM in a sequence-specific fashion. - Minervini, C.F.; Marsano, R.M.; Casieri, P.; Fanti, L.; Caizzi, R.; Pimpinelli, S.; Rocchi, M.; Viggiano, L. (Gene, 2007)
The realization of cross talks between transposable elements of class I and their host genome involves non-histonic chromatin proteins. These interactions have been widely analyzed through the characterization of the gypsy retrotransposon leader region, which holds a particularly strong insulator element, and the proteins required for its function, Su(Hw), Mod(mdg4), and Cp190. Here we provide evidence that a similar interaction should occur between ZAM, a gypsy-like element, and HP1, one of the most extensively studied chromatin proteins. We first assayed the existence of this binding using the yeast cells one-hybrid system and then we verified it in vivo by ChIP assay. In order to characterize the interaction between HP1 and the ZAM 5' untranslated region we performed a series of gel shift analyses. Our observations confirm an HP1 co-operative DNA-binding and display for the first time the HP1 DNA target motif that, we hypothesize, should be one of its nucleation sites.